BS ISO 21243. Radiation protection0. Performance criteria for laboratories performing initial cytogenetic dose assessment of mass casualties in radiological or nuclear emergencies. General principles and application to dicentric assay. (2nd August 2021) - British Standards Institution,
No abstract available